The association of self-injurious behaviour and suicide attempts with recurrent idiopathic pain in adolescents: evidence from a population-based study. Issue 1 (December 2015) - Koenig, Julian; Oelkers-Ax, Rieke; Parzer, Peter; Haffner, Johann; Brunner, Romuald; Resch, Franz; Kaess, Michael
Abstract Background While several population-based studies report that pain is independently associated with higher rates of self-destructive behaviour (suicidal ideation, suicide attempts, and self-injurious behaviour) in adults, studies in adolescents are rare and limited to specific chronic pain conditions. The aim of this study was to investigate the link between self-reported idiopathic pain and the prevalence and frequency of self-injury (SI) and suicide attempts in adolescents. Methods Data from a cross-sectional, school-based sample was derived to assess SI, suicide attempts, recurrent pain symptoms and various areas of emotional and behavioural problems via a self-report booklet including the Youth Self-Report (YSR). Adolescents were assigned to two groups (presence of pain vs. no pain) for analysis. Data from 5, 504 students of 116 schools in a region of South Western Germany was available. A series of unadjusted and adjusted multinomial logistic regression models were performed to address the association of pain, SI, and suicide attempts. Results 929 (16.88%) respondents reported recurrent pain in one of three areas of pain symptoms assessed (general pain, headache, and abdominal pain). Adolescents who reported pain also reported greater psychopathological distress on all sub-scales of the YSR. The presence of pain was significantly associated with an increased risk ratio (RR) for SI (1–3 incidences in the past year: RR: 2.96; >3 incidences: RR: 6.04) and suicide attempts (one attempt: RR: 3.63; multiple attempts: RR: 5.4) in unadjusted analysis. Similarly, increased RR was observed when adjusting for sociodemographic variables. While controlling for psychopathology attenuated this association, it remained significant (RRs: 1.4–1.8). Sub-sequent sensitivity analysis revealed different RR by location and frequency of pain symptoms. Conclusions Adolescents with recurrent idiopathic pain are more likely to report previous incidents of SI and suicide attempts. This association is likely mediated by the presence of psychopathological distress as consequence of recurrent idiopathic pain. However, the observed variance in dependent variables is only partially explained by emotional and behavioural problems. Clinicians should be aware of these associations and interview adolescents with recurrent symptoms of pain for the presence of self-harm, past suicide attempts and current suicidal thoughts. Future studies addressing the neurobiology underpinnings of an increased likelihood for self-injurious behaviour and suicide attempts in adolescents with recurrent idiopathic pain are necessary.